The double and the imaginary of Um rosto noturno, by Reynaldo Moura - Raabe, Camilo Mattar (Revista de Letras, 2017)
The present work intends to study the imaginary and the theme of the double in Um rosto noturno (1946), Reynaldo Moura’s novel (1900 – 1965), considered one of the first intimate writers from Brazil, in activity since 1930´s. Um rosto noturno is the Ulisses’ psychological journey through his symbolic and hermetic diary, composed by somnambulism and hallucination, on a tentative to keep his sanity while his wife was submerging in a fantastic dimension after a car accident that disfigured her face. With symbolist novel characteristics, Um rosto noturno is the most intimate Moura’s work, in which the imaginary construction is the rhetoric’s first objective, structured by the theme of the double, reflecting the symbolical ambiguity and the narrative’s fantastic architecture.